Tris(benzoimidazol)amine (L) complexes of pnictogen(iii) and pnictogen(v) cations and assessment of the [LP]3+/[LPF2]3+ redox couple. Issue 26 (21st June 2018) - Swidan, Ala'aeddeen; Suter, Riccardo; Macdonald, Charles L. B.; Burford, Neil
Abstract : A tris((1-ethyl-benzoimidazol-2-yl)methyl)amine (BIMEt3 ) complex of P 3+ is oxidized with XeF2 to access [PF2 (BIMEt3 )] 3+ representing the first structurally characterized example of a phosphorus(v ) 3+ cation. Abstract : A series of cationic complexes involving a pnictogen(iii ) (Pn = P, As, Sb) centre and the tetradentate ligand tris((1-ethyl-benzoimidazol-2-yl)methyl)amine (BIMEt3 ) have been synthesized and comprehensively characterized. Oxidation of [P(BIMEt3 )] 3+ with XeF2 provides access to [PF2 (BIMEt3 )] 3+ representing the first structurally characterized example of a phosphorus(v ) centred trication.